Effect of layer thickness and tyre footprint in the Flexible pavement design - Kathirgamanathan, P.; Vignarajah, M. (University of Jaffna, 2019)
The accuracy of any pavement deformation modelling depends greatly on the traffic characteristics, pavement structural properties and climate conditions. A clear understanding of structural changes of each layer with respect to the load, thickness of layers, speed and temperature are necessary to model the pavement deformation.
Keywords: Finite element modelling; UMAT; Pavement response